Capabilities of satellite altimetry measurements for assessing the consequences of the Kakhovka hydroelectric power plant dam destruction - Tomchenko, Olha; Magas, Natalia; Sheviakina, Natalia; Zahorodnia, Snizhana; Radchuk, Ihor (Ukrainian journal of remote sensing, 2026)
The destruction of the Kakhovka HPP dam on 6 June 2023 caused one of the largest man-made hydrological disasters in Europe since the 1986 Chornobyl accident: according to UNOSAT, approximately 620 km² of the Lower Dnieper delta was inundated between 6 and 9 June 2023. Limited ground access to frontline and occupied territories makes Earth remote sensing methods practically the only instrument for objective monitoring of such events. This study presents a methodological framework for detecting and assessing the temporal dynamics of inundation through the integration of Hydroweb satellite altimetry data (three virtual stations located 10–33 km downstream of the dam), ground-based hydrological observations (three gauges of the Mykolaiv and Kherson Regional Hydrometeorological Centres), and radar (Sentinel-1) and optical (Sentinel-2, Landsat-9) satellite imagery. For the ground gauges, regular twice-daily observations and hourly measurements collected during the month after 6 June 2023 were used, enabling a detailed reconstruction of the onset, peak, and duration of the anomalous water-level rise. To overcome the incompatibility of vertical reference systems (EGM2008 and the Baltic 1977 height system), water-level anomalies were calculated as ΔH = H_i − H̄_; the baseline period selected was January–May 2023, with twice the standard deviation of the baseline series used as the statistical significance threshold. Statistically significant anomalous water-level rises were detected at all six stations from 6 June 2023. The largest anomalies were recorded at Hydroweb station 6 ( 10.5 m, 10 km downstream of the dam), station 5 ( 6.8 m, 17 km), and station 4 ( 4.1 m, 33 km), with gradual attenuation toward the estuary. The duration of the anomalous state at downstream stations exceeded that at upstream stations, reflecting the hydrodynamics of lowland rivers after dam breaches. SAR and optical analysis confirmed the spatial extent of flooding of riparian and floodplain areas. The proposed methodology is suitable for rapid monitoring of man-made disasters in inaccessible or occupied territories and provides a basis for further environmental damage assessment. Author Contributions: Conceptualization, O. V. Tomchenko; methodology, N. A. Sheviakina; data systematization and analysis, N. I. Magas and S. A. Zahorodnia, І.V.Radchuk I; preparation of visual materials, O. V. Tomchenko; drafting of the original manuscript, N. A. Sheviakina; review and editing, S. A. Zahorodnia and N. I. Magas; visualization, O. V. Tomchenko. All authors have read and agreed to the final version of the manuscript. Funding: The study was carried out as part of the scientific research projects: "Development of a software complex to provide satellite monitoring of marine ecosystems" (2026–2027), RC № 0126U001826, and "Development and improvement of methods and technologies of geospatial modeling to solve thematic problems of remote sensing" (2023–2027), RC № 0123U100684. Disclosure of AI use: We confirm that no generative artificial intelligence tools were used in the preparation of this manuscript. Data Availability Statement: The data can be provided by the authors upon reasonable request. Acknowledgments: The authors are grateful to the reviewers and editors for their valuable comments, recommendations, and attention to this work. Conflicts of Interest: The authors declare no conflict of interest.